Learning decision catalogues for situated decision making: The case of scoring systems - Heid, Stefan; Hanselle, Jonas Manuel; Fürnkranz, Johannes; Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Learning decision catalogues for situated decision making: The case of scoring systems - Heid, Stefan; Hanselle, Jonas; Fürnkranz, Johannes; Hüllermeier, Eyke (International Journal of Approximate Reasoning)

'Mapping the Pott': Online-Befragung zur Mehrsprachigkeit der Lehramtsstudierenden der UA Ruhr - Günesli, Habib; Sotkov, Mihail

The Value of Reputation Systems in Business Contexts–A Qualitative Study Taking the View of Buyers - Hemmrich, Simon; Schäfer, Jannika Marie; Hansmeier, Philipp; Beverungen, Daniel (Proceedings of the 57th Hawaii International Conference on System Sciences)
Reputation systems for companies to rate each other's performance are largely unexplored in research and hardly available in practice. However, these systems are relevant for prospective buyers to find a trustworthy seller. This observation applies especially to short-lived business relationships where fulfilling the performance promise is subject to a high degree of uncertainty. This paper explores the value of a reputation system for a business-to-business (B2B) context and focuses on three novel solutions for designing reputation systems. These solutions include selling ratings, conducting ratings as payments, and employing a counter-rating mechanism. We interview buyers to fathom the added value of these solutions in different contexts. Our findings suggest that such a system is useful for companies acting in less transparent markets and also helps when companies already have a good market overview. Depending on the market conditions and business context, the perceived value of the proposed system varies.
Keywords: Electronic Marketing; business-to-business; new design approach; reputation systems; value for buyers.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette E. (European Journal of Nutrition)

Association between glucose dips and the feeling of hunger in a dietary intervention study among students with early and late chronotype-secondary analysis of a randomized cross-over nutrition trial - Stutz, Bianca; Goletzke, Janina; Krueger, Bettina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette E. (Appetite)

MULTISCALE ENTROPY ANALYSIS IN MOBILE EEG: COULD IT HAVE A POTENTIAL USE IN REAL-WORLD SETTINGS? - Piskin, Daghan Yüksel; Cobani, Gjergji; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen

Vernakulärer Code oder die Geister, die der Algorithmus rief - digitale Schriftlichkeit im Kontext von sozialen Medienplattformen - Schulz, Christian (Digitale Schriftlichkeit – Progammieren, Prozessieren und Codieren von Schrift)

Das Unhörbare sehen - Ultraschall mittels Schlierentechnik visualisieren - Hetkämper, Tim; Claes, Leander; Henning, Bernd (Akustik Journal)

Filter – Medienwissenschaftliche Symposien der DFG

Fast Convergence of Inertial Multiobjective Gradient-Like Systems with Asymptotic Vanishing Damping - Sonntag, Konstantin; Peitz, Sebastian (SIAM Journal on Optimization)
We present a new gradient-like dynamical system related to unconstrained convex smooth multiobjective optimization which involves inertial effects and asymptotic vanishing damping. To the best of our knowledge, this system is the first inertial gradient-like system for multiobjective optimization problems including asymptotic vanishing damping, expanding the ideas previously laid out in [H. Attouch and G. Garrigos, Multiobjective Optimization: An Inertial Dynamical Approach to Pareto Optima, preprint, arXiv:1506.02823, 2015]. We prove existence of solutions to this system in finite dimensions and further prove that its bounded solutions converge weakly to weakly Pareto optimal points. In addition, we obtain a convergence rate of order \(\mathcal{O}(t^{-2})\) for the function values measured with a merit function. This approach presents a good basis for the development of fast gradient methods for multiobjective optimization.
Keywords: multiobjective optimization; Pareto optimization; Lyapunov analysis; gradient-likedynamical systems; inertial dynamics; asymptotic vanishing damping; fast convergence

Digitales und prädiktives Kompetenzmanagement

Imagining and Governing Artificial Intelligence – the Ordoliberal Way: An Analysis of the National Strategy ‘AI Made in Germany’ - Hälterlein, Jens (AI & Society)

“Meaningful Human Control” and Complex Human-Machine Assemblages – On the Limits of Ethical AI Principles in the Context of Autonomous Weapons Systems - Hälterlein, Jens; Weber, Jutta (Ethics and Armed Forces)

Biometrische Gesichtserkennung – Technologischer Solutionismus für mehr „Sicherheit“ - Hälterlein, Jens (CILIP Bürgerrechte & Polizei)

Fähigkeitsprofile im Physikdidaktischen Wissen mithilfe von Machine Learning - Zeller, Jannis; Riese, Josef (Frühe naturwissenschaftliche Bildung, Tagungsband der GDCP Jahrestagung 2023)
Das Fachdidaktische Wissen (FDW) wird als zentrale Komponente des Professionswissens von Lehrkräften bereits lange intensiv untersucht. Bislang liegen Ergebnisse zu Zusammenhängen des FDW mit anderen Professionswissensbereichen, zur Performanz in prototypischen Handlungssituationen und erste datengestützte inhaltlich-hierarchische Analysen auf Basis von Item Response Modellen (IRT-Modellen) vor. Im Zusammenhang mit einem projektübergreifend durchgeführten Vergleich entsprechender IRT-Modelle haben sich jedoch Limitationen bei der Vereinbarkeit und der inhaltlichen Reichhaltigkeit entsprechender Ergebnisse gezeigt, wie im Beitrag vorgestellt wird . Daher werden Analysemethoden aus dem Bereich des Machine Learning (unsupervised) vorgeschlagen, welche im Gegensatz zu IRT-Modellen auch nicht-hierarchische inhaltliche Strukturen aufdecken können. Es werden Ergebnisse entsprechender Clusteranalysen sowie Analysepläne zur Unterstützung dieser auf Basis der authentischen Sprachproduktionen von Proband:innen mithilfe von Natural Language Processing vorgestellt.
Keywords: Physikdidaktisches Wissen; Fähigkeitsprofile; Machine Learning

Realizing Concurrency on Top of the Microkernel seL4 via Improved Threads - Delgado Steuter, Dominik

Time and Transformation in Autobiography: Candia McWilliam’s What to Look for in Winter: A Memoir in Blindness - Mildorf, Jarmila (Perspektywy Kultury / Perspectives on Culture)

On the Shape Containment Problem within the Amoebot Model with Reconfigurable Circuits - Artmann, Matthias

The Interplay of Sound Tapestry and Music in the 1992 German Radio Play Adaptation of J.R.R. Tolkien’s The Lord of the Rings - Mildorf, Jarmila (Word, Sound and Music in Radio Drama)